Regulation of xylem cell fate - Kondo, Yuki; Tamaki, Takayuki; Fukuda, Hiroo (Frontiers in Plant Science, 2014)
The vascular system is deliberately placed throughout the plant body for transporting water, nutrients, and signaling molecules. During vascular development, xylem, phloem, and procambial/cambial cells are differentiated in a spatiotemporally organized manner. Up to now, various key regulators for xylem cell patterning and differentiation such as auxin, cytokinin, CLE peptides, microRNAs, HD-ZIPIIIs, VNDs, and moving transcription factors SHR and AHLs have been discovered. Recent studies are revealing functional interactions among such factors to eventually determine the xylem cell fate. This review focuses on networks of various regulators underlying xylem cell fate determination in root vascular development.